Enaminones as Building Blocks in Heterocyclic Syntheses: Reinvestigating the Product Structures of Enaminones with Malononitrile. A Novel Route to 6-Substituted-3-Oxo-2,3-Dihydropyridazine-4-Carboxylic Acids - Mohamed Hilmy Elnagdi; Amal Al-Enezi; Mervat Mohammed Abdelkhalik; Abdul-Aziz Alnajjar (Molecules, 2008)
The reported structures of reaction products of enaminones with malononitrile in ethanolic piperidine are revised. A novel route to 2,3-dihydropyridazine-4-carboxylic acids 4a-c via reactions of 2-cyano-5-(dimethylamino)-5-arylpenta-2,4-dienamides 8a-c with nitrous acid or with benzenediazonium chloride is reported. Compounds 8a-c are converted to 1,2-dihydropyridine-3-carboxylic acid and 1,2-dihydropyridine-3-carbonitrile derivatives upon reflux in EtOH/ HCl and in AcOH.